Implementasi Customer Service Bri Melalui Instagram Untuk Meningkatkan Kepuasan Nasabah Saat Pandemi Covid 19 - Eki Chandra Nur Iman; Adibah Natasya (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2022)
The purpose of this study was to determine the application of BRI customer service by utilizing news media (Instagram) to increase customer satisfaction during the Covid-19 pandemic. This study took a quantitative approach to its investigation. This study was carried out at Bank BRI. Random sampling is the sample approach used in this study. In this survey, 100 participants who are Bank BRI clients were asked to participate. The smart PLS program aided the data analysis with a structural approach to the Equation Model (SEM). The results of this study are that customer service has a significant positive effect on customer satisfaction, customer service can increase engagement on social media, Instagram news media has a significant positive effect on customer satisfaction.